The Influence of Non-Physical Work Environment on Gen Y Employee Engagement: Mediating Roles of Perceived Organizational Support and Workplace Well-being - Tamboto, Grace Reine Pingki; Sugiarto, Agus (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This study aims to determine the influence of the non-physical work environment on employee engagement, both directly and indirectly, through perceived organizational support and well-being at work as mediating variables. This research uses an explanatory research type with a sample of 104 people selected using a purposive sampling method. The data were measured using SEM-PLS with SmartPLS 3 software. The research results show that the non-physical work environment has a positive effect on perceived organizational support, workplace well-being, and employee engagement through workplace. However, the influence of the non-physical work environment on employee engagement and the influence of the non-physical work environment on employee engagement through perceived organizational support did not have a positive effect.